KESETARAAN UJI PEPIN DAN LUCAS-LEHMER - Yulismansyah '; Sri Gemawati; Musraini M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Pepin test provides a necessary and sufficient condition for a Fermat number to be a prime. Lucas-Lehmer test provides a necessary and sufficient condition for a Mersenne number to be a prime. In this article, we review a part of the work of Jaroma [European Journal of Pure and Applied Mathematics Vol. 2, No. 3, 2009, (352-360)] that is the equivalence structure of Pepin test and Lucas-Lehmer test through Lehmer sequences so that both test can be used to check when a Fermat number or a Mersenne number to be a prime.